An epistemology of patient safety research: a framework for study design and interpretation. Part 1. Conceptualising and developing interventions. Issue 3 (2nd June 2008) - Brown, C; Hofer, T; Johal, A; Thomson, R; Nicholl, J; Franklin, B D; Lilford, R J
Abstract : This is the first of a four-part series of articles examining the epistemology of patient safety research. Parts 2 and 3 will describe different study designs and methods of measuring outcomes in the evaluation of patient safety interventions, before Part 4 suggests that "one size does not fit all". Part 1 sets the scene by defining patient safety research as a challenging form of service delivery and organisational research that has to deal (although not exclusively) with some very rare events. It then considers two inter-related ideas: a causal chain that can be used to identify where in an organisation's structure and/or processes an intervention may impact; and the need for preimplementation evaluation of proposed interventions. Finally, the paper outlines the authors' pragmatist ontological stance to patient safety research, which sets the philosophical basis for the remaining three articles.